Activated and nonactivated MSCs increase survival in humanized mice after acute liver injury through alcohol binging. Issue 7 (5th March 2022) - Hernandez, Juan Carlos; Yeh, Da‐Wei; Marh, Joel; Choi, Hye Yeon; Kim, Julia; Chopra, Shefali; Ding, Li; Thornton, Matthew; Grubbs, Brendan; Makowka, Leonard; Sher, Linda; Machida, Keigo
Abstract: The ability of the liver to regenerate after injury makes it an ideal organ to study for potential therapeutic interventions. Mesenchymal stem cells (MSCs) possess self‐renewal and differentiation properties, as well as anti‐inflammatory properties that make them an ideal candidate for therapy of acute liver injury. The primary aim of this study is to evaluate the potential for reversal of hepatic injury using human umbilical cord–derived MSCs. Secondary aims include comparison of various methods of administration as well as comparison of activated versus nonactivated human umbilical cord stem cells. To induce liver injury, humanized mice were fed high‐cholesterol high‐fat liquid diet with alcohol binge drinking. Mice were then treated with either umbilical cord MSCs, activated umbilical cord MSCs, or a placebo and followed for survival. Blood samples were obtained at the end of the binge drinking and at the time of death to measure alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels. Histology of all mouse livers was reported at time of death. Activated MSCs that were injected intravenously, intraperitoneally, or both routes had superior survival compared with nonactivated MSCs and with placebo‐treated mice. AST and ALT levels were elevated in all mice before treatment and improved in the mice treated with stem cells. Conclusion: Activated stem cells resulted in marked improvement in survival and in recovery of hepatic chemistries. Activated umbilical cord MSCs should be considered an important area of investigation in acute liver injury. Abstract : Activated stem cells resulted in marked improvement in survival and in recovery of hepatic chemistries. Activated umbilical stem cells should be considered an important area of investigation in acute liver injury.